A concise handbook of mathematics, physics, and engineering sciences - Polianin, A. D. (Andrei Dmitrievich); Chernoutsan, A. I. (Boca Raton, Fl. : Chapman & Hall/CRC, 2011)
Includes bibliographical references and index